Islam and Hated Intolerance: In the light of teachings of Holy Qur’an and Prophet Muḥammad’s Sunnah (A Descriptive and Analytical Study) - Lubis, Tonang (Advances in Social Sciences Research Journal, 2020)
Islam does not allow the nervousness and the mutual contempt and hatred that follows it between the tribes, peoples and nations, but rather, on the contrary, heralds the friendship and brotherhood among Muslims, tolerance of religions and dialogue between the human beings. Islam has achieved the compatibility and harmony between a large numbers of people of different races and lineages. So Islam liberated the individual from the narrow tribal framework in a wider and welcoming society that included the tribe members as well as the members of other tribes. When Islam included the tribes in a society, its concern was to fight nerve tendencies and the tribal spirit. It made the original principles not to differentiate between the people on the basis of genealogy or the races or the colors, because the differentiation in Islam is based on the faith, piety and goodness. In this article, we dealt with the definition of nervousness in terms of language and convention, a historical background of the intolerance and its origin, signs of intolerance, causes of intolerance, types of intolerance: Intellectual intolerance, doctrinal intolerance, gradient or class intolerance, intolerance to sanctify the inherited past, partisan intolerance, and tribal intolerance. Tribal intolerance is from the pre-Islamic biography, then we dealt with the issue of treating hateful intolerance mentioned in the Holy Qur’an and the noble Prophet’s Sunnah. At the end of the article, we mentioned a number of results for this research.